Escape from States of Loss and Suffering (apāya) through Releasing the Fetters (saṁyojana) - Klunsupa, Senior Col.Dr.Tuenjai (Journal of the Philosophy and Religion Society of Thailand, 2023)
This work is proposing the path leading to the cessation of suffering which aims to study the concept of the fetters (saṁyojana) in Theravāda scriptures, to study and analyze the principles, the practice of the path, and the practices of systematically releasing the fetters (saṁyojana) leading to escape from states of loss and suffering (apāya) to enlightenment (nibbāna). The following are the findings: the Buddha handles the defilements by classifying these into a tenfold group called saṁyojana (fetters) that can be destroyed through the practice of the noble eightfold path. The practices are mental development (citta-bhāvanā) which is composed of tranquility development (samatha-bhāvanā) and insight development (vipassanā-bhāvanā). The four foundations of mindfulness are the crucial means to realize the noble eightfold path and to practice for releasing the fetters. The noble eightfold path is to be practiced in accordance with the teaching of forest monks that of Luang Pu Mun and Phra Ajahn Chah in Thai society. Also relevant is the dhamma and discipline will be the teacher after the Buddha passed away. In this dhamma and discipline the noble eightfold path is found, and in it, are to be found disciples of the first, second, third and fourth grade. If the monks were to live the life to perfection, the world would not lack for arahants. Keywords: Escape, States of Loss and Suffering, Releasing, Fetters, Noble eightfold path, Foundation of mindfulness, Enlightenment, Nibbāna.